Alternative technologies in cervical cancer screening: a randomised evaluation trial - Anttila, Ahti (BioMed Central, 2006)
BACKGROUND: Cervical cancer screening programmes have markedly reduced the incidence and mortality rates of the disease. A substantial amount of deaths from the disease could be prevented further by organised screening programmes or improving currently running programmes. METHODS/DESIGN: We present here a randomised evaluation trial design integrated to the Finnish cervical cancer screening programme, in order to evaluate renewal of the programme using emerging technological alternatives. The main aim of the evaluation is to assess screening effectiveness, using subsequent cancers as the outcome and screen-detected pre-cancers as surrogates. For the time being, approximately 863,000 women have been allocated to automation-assisted cytology, human papillomavirus (HPV) DNA testing, or to conventional cytology within the organised screening programme. Follow-up results on subsequent cervical cancers will become available during 2007–2015. DISCUSSION: Large-scale randomised trials are useful to clarify effectiveness and cost-effectiveness issues of the most important technological alternatives in the screening programmes for cervical cancer.